2013
DOI: 10.1016/j.febslet.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PKCε by miR‐143 regulates cell apoptosis in lung cancer

Abstract: a b s t r a c tNon-small cell lung cancer (NSCLC) is one of the most common causes for lung cancer and cancer-related death. The imbalance between cell proliferation and apoptosis was suggested to play an important role in cancer pathogenesis and PKCe is one of the widely recognized targets. Here, we demonstrate that miR-143 is aberrantly downregulated in NSCLC tissue and negatively correlates with expression of PKCe. We show that miR-143 specifically targets the 3 0 -UTR of PKCe and regulates its expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 38 publications
4
34
0
1
Order By: Relevance
“…On the other hand, miR-143 targets MDM2, which negatively controls the stability and transcriptional activity of p53. Similar to miR-34a, miR-143 which resides at chromosome 5q, is often down regulated or deleted in a number of malignancies (Lui et al, 2007;Volinia et al, 2010;Zhang et al, 2013b;Ng et al, 2014). Moreover, miR-143 was found to be down regulated in OSCC animal model and in human head and neck squamous cell carcinoma (HNSCC) (Yu et al, 2009;Hui et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, miR-143 targets MDM2, which negatively controls the stability and transcriptional activity of p53. Similar to miR-34a, miR-143 which resides at chromosome 5q, is often down regulated or deleted in a number of malignancies (Lui et al, 2007;Volinia et al, 2010;Zhang et al, 2013b;Ng et al, 2014). Moreover, miR-143 was found to be down regulated in OSCC animal model and in human head and neck squamous cell carcinoma (HNSCC) (Yu et al, 2009;Hui et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After 48 h of hypoxia administration, cells were collected, washed with PBS and then incubated with 10 µL of Annexin V-FITC and 5 µL of PI for 30 min at room temperature in the dark. Apoptotic cells were measured by Epics XL flow cytometer (Beckman Coulter, USA) [22].…”
Section: Cell Apoptosis Assaymentioning
confidence: 99%
“…The imbalance between cell proliferation and apoptosis has been implicated to serve key roles in cancer pathogenesis (6,7). Accumulating evidence has indicated that microRNAs (miRNAs or miRs) serve a role in a number of cancer processes, including lung cancer (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%